Three Worlds of Collective Human Experience: Individual Life, Social Change, and Human Evolution - Shaw, Victor N. (Springer International Publishing : Imprint: Springer, 2019)
This book explores three worlds shared by the humans in their collective experiences. It identifies and explores the world of commonsense, the world of religion, and the world of science as three essential dimensions of human experience. The book helps understand that humans can gain comfort and pleasure in commonsense, achieve meaning and purpose from religion, and attain truth and rationality through science. It actively applies theories to and develops theoretical explanations from different domains or situations of human existence. This book is of interest to theorists, researchers, instructors, and students across major academic disciplines in the humanities and social sciences.